Upcycling of CO2 into sustainable hydrocarbon fuels via the integration of Fe-based Fischer-Tropsch synthesis and olefin oligomerization: A comparative case study - Gao, Ruxing; Wang, Lei; Zhang, Leiyu; Zhang, Chundong; Jun, Ki Won; Ki Kim, Seok; Park, Hae Gu; Zhao, Tiansheng; Gao, Ying; Zhu, Yuezhao; Wan, Hui; Guan, Guofeng (Fuel, 2022)
Power-to-X (PtX) technologies, especially for the Power-to-Liquids (PtL) and Power-to-Gas (PtG) have attracted extensive attention recently, as promising pathways for carbon upcycling via converting CO2 into high-value products including liquid fuels and substitute natural gas (SNG). Herein, aiming at further improving the PtX process efficiency, we proposed two novel PtL/PtG hybrid processes, namely an indirect process (with RWGS unit) and a direct process (without RWGS unit) by integrating Fe-based Fischer-Tropsch synthesis (FTS) and olefin oligomerization technologies, which co-produce syncrude and SNG. Both process simulation and techno-economic analysis were implemented to evaluate the overall process performances, through various indicators involving technical indicators (e.g., syncrude production, energy efficiency, and net CO2 reduction), and economic indicators such as total capital investment, net CO2 reduction costs together with total product costs. Both proposed PtL/PtG processes are efficient in converting CO2 into valuable hydrocarbon fuels, and the syncrude production and total product revenues of indirect process are 2.35–14.58% and 7.55–8.51% higher than those of the direct process, respectively. Whereas, the direct process has lower net CO2 reduction cost of 206.09 $/tonne CO2. Moreover, the present PtL/PtG processes have higher syncrude production and total product revenues than those of our previous studies including a direct PtL/PtG process coupled with Fe-based FTS and two indirect PTL/PTG processes combined with RWGS and Fe/Co-based FTS reaction, with rates of 30.95 and 12.73% at most.
Keywords: CO 2 reduction; CO2 hydrogenation; Fe-based; Hydrocarbon fuel; Liquid power; Olefins oligomerization; Power; Process simulations; Syncrude; Techno-Economic analysis; CO2 hydrogenation; Fischer-Tropsch synthesis; Olefin oligomerization; Process simulation; Techno-economic analysis